Density of Mexican woods by vegetation type based on J. Rzedowski’s classification: compilation - Ordóñez Díaz, José Antonio Benjamín; Galicia Naranjo, Adolfo; Venegas Mancera, Nuria Julieta; Hernández Tejeda, Tomás; Ordóñez Díaz, María de Jesús; Dávalos-Sotelo, Raymundo (Instituto de Ecología, A.C., 2015)
We conducted a literature review of the basic density of diverse species focused on timber species in Mexico by vegetation cover type. Ecosystems and species included are based on the classification of the vegetation of Mexico prepared by J. Rzedowski (1978) that even tough it is still considered the primary source of information on vegetation types, it is necessary to take into account that there are new developments in the taxonomic identification and/or reclassification. Whereupon, we list here the wood density values for 611 species and 785 species are identified as without information at the time. Also, we provide data of minimum and maximum values of density by ecosystem type, and the list corresponding to density by specie (sp.), and by ecosystem type. The knowledge of wood density, not only allows the better use of wood as a natural resource, but it becomes important in the conversion of real stock volume (m3) to biomass (t) and in particular to estimate the content, capture or carbon sequestration, where, by having the value of wood density, allows more accurate estimates (biomass and carbon concentrations). This fact has gained importance to the carbon sequestration market as a conservation measure of plant cover, payment for environmental services, in particular as a strategy for climate change mitigation and especially for greenhouse gases emission inventories and MRV of REDD’s projects.